Current understanding on inferior quality of liver grafts by donation after circulatory death based on multi-omics data - Zhou, Yifeng; Que, Ting; Yu, Lu; Que, Shuping; Xu, Jun; Liu, Zhengtao (Frontiers in Immunology, 2025)
Given the inevitable hypoxia and reperfusion injury that occur in organs donated after circulatory death (DCD), the quality and function of these organs are significantly compromised, greatly limiting their application in clinical organ transplantation. Recently, the advancement of functional omics technologies has enabled us to deeply analyze the mechanisms underlying DCD donor organ damage from multiple perspectives. This review systematically integrates the studies from transcriptomics, proteomics, and metabolomics to reveal the key biological mechanisms associated with the declines in DCD donor organ quality, including oxidative stress, inflammatory responses, cell death pathways, and metabolic disturbances. Additionally, we summarized emerging therapeutic strategies based on findings from omics perspectives, offering new possibilities to improve the quality of DCD organ for better transplant prognosis. Finally, we discussed the challenges in current research and future directions to provide scientific evidence for clinical practice and promote the application of DCD donors in organ transplantation.